Bahasa Indonesia PENGARUH TINGKAT DEPRESI TERHADAP KEMANDIRIAN ACTIVITIES OF DAILY LIVING (ADL) PADA LANSIA - w ibowo (Jurnal Keperawatan Malang, 2018)
AbstractThe aging process experienced by the elderly will result in physical and mental deterioration. Mentaldisorders that are often found in the elderly are anxiety and depression that lead to deterioration ofquality of life which has implications for independence in carrying out daily activities or ADL (Activitiesof Daily Living). Research methods using descriptive correlation research with cross sectional researchdesign that aims to see the relationship of the level of depression of the elderly to the level ofindependence of the elderly in getting the needs of Activity Daily Living (ADL). The population in thisstudy were the elderly who came to posyandu, sampling technique used was total sampling with thenumber of samples counted 76 respondents using Geriatric Depression Scale (GDS) and KATZ Index. The statistical test used is non parametric statistic test, that is Spearmen Rank Correlation test using SPSS 20 for significance or Sig. (2-tailed) of 0.413. Because the value of Sig. (2-tailed) 0,413> 0,05level (2-tailed) hence there is no significant correlation between depression level and degree ofindependence in elderly. Based on the results of this study the independence of the elderly is largely determined by the regularity in doing ADL and the elderly who live with family is a support system for theelderly in the face of changes due to the aging process. Keywords: Depression, Activities of Daily Living, Elderly